2008
DOI: 10.1007/s00586-008-0829-0
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in spinal cord injury

Abstract: Spinal cord injury (SCI) is a devastating condition for individual patients and costly for health care systems requiring significant long-term expenditures. Cytokine erythropoietin (EPO) is a glycoprotein mediating cytoprotection in a variety of tissues, including spinal cord, through activation of multiple signaling pathways. It has been reported that EPO exerts its beneficial effects by apoptosis blockage, reduction of inflammation, and restoration of vascular integrity. Neuronal regeneration has been also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 74 publications
1
24
0
2
Order By: Relevance
“…It was previously considered that EPO is only a endocrine hormone acting on hematopoietic cells. However, EPO has been demonstrated to be a type of tissue protection factor, which exerts neurotrophic and neuroprotective effects (2,3). Yuan et al (4) observed the effects of erythropoietin on the differentiation of embryonic cerebral cortex neural stem cells of rats cultured in vitro, the results indicated that erythropoietin is able to promote the differentiation of neural stem cells into neurons.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously considered that EPO is only a endocrine hormone acting on hematopoietic cells. However, EPO has been demonstrated to be a type of tissue protection factor, which exerts neurotrophic and neuroprotective effects (2,3). Yuan et al (4) observed the effects of erythropoietin on the differentiation of embryonic cerebral cortex neural stem cells of rats cultured in vitro, the results indicated that erythropoietin is able to promote the differentiation of neural stem cells into neurons.…”
Section: Introductionmentioning
confidence: 99%
“…EPO has been claimed to promote axonal regeneration to increase neoangiogenesis, to inhibit apoptosis, to have anti-inflammatory effects, to have anti-ischemic effects, to decrease microglial infiltration, to inhibit scar formation, and thereby may contribute to neurological improvement. [15][16][17][18][19] Nevertheless, the exact mechanism of neuroprotection of EPO is still not certain. Even if key determinant to EPO secretion is hypoxia, EPO receptors are more sensitive to pro-inflammatory cytokines such as tumor necrosis factor-1 and interleukin-1 beta than hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to develop new drugs that provide long-term, safe and effective effects against spinal cord I-R injury. Recent research has shown that EPO acts as a new neurotrophic and neuroprotective agent in different experimental settings ranging from in vitro neuronal cell culture model to in vivo animal models [5][6][7][8][9][10][11][12][13] . Most significantly, administration of EPO or its analogues has proven effective against SCI [12] .…”
Section: Discussionmentioning
confidence: 99%